Modeling and control of 41-level inverter using best switching angles calculation method - Alla Eddine Toubal Maamar; M'hamed Helaimi; Rachid Taleb; Abdelatif Gadoum (International Journal of Applied Power Engineering (IJAPE), 2020)
In this paper, analysis and modeling of a single-phase H-bridge forty-one level inverter are con sidered. The control of proposed inverter by equal-phase and half-height methods is implemented. MATLAB/Simulink environments are used to simulate the model an d show obtained results of waveforms with FFT analysis. Eventually, the total harmonic distortion obtained for each level with the two methods is presented, comparatively, for a comparison.